Carbothermal Reduction of Iron Ore in Its Concentrate-Agricultural Waste Pellets - Zhulin Liu; Xuegong Bi; Zeping Gao; Wei Liu (Advances in Materials Science and Engineering)
Carbon-containing pellets were prepared with the carbonized product of agricultural wastes and iron concentrate, and an experimental study on the direct reduction was carried out. The experimental results demonstrated that carbon-containing pellets could be rapidly reduced at 1200 to 1300°C in 15 minutes, and the proper holding time at high temperature was 15 to 20 min. The degree of reduction gradually increased with temperature rising, and the appropriate temperature of reducing pellets was 1200°C. The weight loss rate and reduction degree of pellets increased with the rise of carbon proportion, and the relatively reasonable mole ratio of carbon to oxygen was 0.9. A higher content of carbon and an appropriate content of volatile matters in biomass char were beneficial to the reduction of pellets. The carbon-containing pellets could be reduced at high speeds in the air, but there was some reoxidization phenomenon.